Doctor Who. Series nine, Part one [videorecording (DVD)] - Capaldi, Peter; Coleman, Jenna, 1986- (BBC, 2015)
Now that the Doctor and Clara have established a dynamic as a partnership of equals, they're relishing the fun and thrills that all of space and time has to offer. Tangling with ghosts, Vikings and the ultimate evil of the Daleks, they embark on their biggest adventures yet.